Asteroid lightcurve phase shift from rough‐surface shadowing. (25th February 2013) - Wilkman, Olli; Muinonen, Karri
Abstract We have simulated asteroid lightcurves for simple shape models using a realistic surface scattering law. The scattering law includes a shadowing function computed with numerical ray‐tracing. We computed lightcurves in a variety of illumination geometries for both the traditional Lommel–Seeliger law and our seminumerical law. We observe a shift in the rotational phase of the lightcurves, which depends on the parameters of the scattering law as well as the illumination geometry and the direction of the spin axis of the asteroid. This phase shift is always zero at opposition, and can be as large as 10° for illumination geometries typical for Main Belt asteroids. The phase shift has implications on the accuracy of other results which are based on asteroid lightcurve analysis, such as spin‐state or shape determination.